Harnessing Potentials of Social Media in Transforming Businesses - Gaur, Loveleen; Anshu, Kumari (International Journal of Engineering and Technology, 2018)
Media and technology has undergone radical transformation with time pertaining to change in requirements, technology up gradation, usefulness, using ease, accessibility etc. The main objective of mass media is to propagate facts and figures, generate consciousness and inform the community. Social media is regarded to be the subsequent prime revolution in the arena of communication. Social media is also an integral component of promotion and advertising campaigns, disseminating consciousness, marketing which is efficiently applied by startups and adept companies to generate a launching pad or stage for themselves. Progress in technology has enabled many businesses to reach mass or their fundamental customer base in no time and more effortlessly communicate with them which ultimately determine their goals and incline them towards buying judgments.Â Â